Can oral health education be delivered to high‐caries‐risk children and their parents using a computer game? – A randomised controlled trial. Issue 6 (4th January 2017) - Aljafari, Ahmad; Gallagher, Jennifer Elizabeth; Hosey, Marie Therese
Abstract : Background: Families of children undergoing general anaesthesia (GA) for caries management requested that oral health advice is delivered using audio‐visual media. Objective: To compare an oral health education computer game to one‐to‐one education. Design: A blind randomised controlled trial of 4‐ to 10‐year‐old children scheduled for GA due to caries. Primary outcome measures were (1) parent and child satisfaction with education method; (2) improvements in child's dietary knowledge; and (3) changes in child's diet and toothbrushing habits. Measures were taken at baseline, post‐intervention, and three months later. Results: One hundred and nine families took part. Both methods of education were highly satisfactory to children and parents. Children in both groups showed significant improvement in recognition of unhealthy foods immediately post‐education ( P < 0.001). Fifty‐five per cent of all participants completed telephone follow‐up after 3 months and reported improvements in diet, including reducing sweetened drinks ( P = 0.019) and non‐core foods ( P = 0.046) intake, with no significant differences between the groups. Children reported twice‐daily toothbrushing but no changes in snack selection. Attendance for a 3‐month dental review was poor (11%). Conclusion: Oral health education using a computer game can be as satisfactory and as effective in improving high‐risk‐children's knowledge as one‐to‐one education. The education received can lead to the positive dietary changes in some families.